Inexperienced or overconfident? - Veikkolainen, Jussi (My University, 2017)
The objective of the research is to study behavioral strategy and especially the interpretation of the well-known failures. The research question is as follows: Are there factors, which dictate who will interpret a failure as a consequence of an inexperience instead of an overconfidence? The justification for the research is the need to determine suitable and forgiving environment to enable learning from the failures. The theoretical framework will be based on the strategic management and entrepreneurship. Secondly, the study will have its broader perspective on the relationship between heuristics and cognitive biases. And thirdly, the research gap is in the intersection of experience and overconfidence. The study exploits positivist research philosophy and a deductive approach relying heavily on the existing theoretical base. The study seeks to develop a hypotheses, which are then tested with the collected data. The purpose of the research is a combination of an explanatory and exploratory perspectives. Furthermore, the quantitative, cross-sectional data is collected with a structured and controlled survey and analyzed with descriptive and inferential statistics. The study showcased the difference in judgment of the failures made by a distinguished person versus an anonymous group. There seems to be a tendency to interpret the failure made by a distinguished person as the consequence of an overconfidence and vice versa. The education, position and industry seem to be the factors, which dictate the judgment. Higher education and position incurs tendency to interpret failures made by an anonymous group as consequences of an inexperience instead of an overconfidence. Furthermore, especially observers working on the administrative, culture and communications, social services or technology sector seem to acknowledge the influence of an inexperience. The implication of this result is that these sectors might provide suitable environment to learn from the failures, but only if the failures are done by an anonymous group. However, the study has several limitations (limited and biased sample), which constrain generalizations or creation of new theories.
Keywords: experience; overconfidence; heuristics; cognitive biases; entrepreneur; strategy; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kasvuyrityksen johtamisen maisteriohjelma|